Association of blood pressure classification using the 2017 ACC/AHA guidelines with the progression of coronary artery calcification. (11th May 2021) - Won, KB; Park, EJ; Chun, EJ; Sung, J; Jung, HO; Chang, HJ
Abstract: Funding Acknowledgements: Type of funding sources: None. Aims: The recent American College of Cardiology/American Heart Association guidelines reinforced the criteria for diagnosis of hypertension. We assessed the association of this reinforced criteria with coronary artery calcification (CAC) progression in asymptomatic adults according to different age groups. Methods and results: We included 10, 839 asymptomatic Korean adults (23.4% aged ≤45 years) who underwent at least two coronary artery calcium score (CACS) evaluations between 2012 and 2016. All participants were categorised into normal blood pressure (BP) (untreated systolic/diastolic <120/<80 mmHg), elevated BP (untreated systolic/diastolic 120–129/<80 mmHg), stage 1 hypertension (untreated systolic/diastolic BP 130–139/80–89 mmHg), or stage 2 hypertension (systolic/diastolic BP ≥140/≥90 mmHg or taking anti-hypertensive medication) groups. CAC progression was defined as a difference ≥2.5 between the square roots (√) of the baseline and follow-up CACSs (Δ√transformed CACS). During a mean 3.3-year follow-up, the incidence of CAC progression was 13.5% and 36.3% in groups with ≤45 and >45 years, respectively. After multivariable adjustment for sex, diabetes, dyslipidaemia, obesity, current smoking, and baseline CACS, hazard ratios (95% confidence interval) for CAC progression versus normal BP in elevated BP, stage 1 hypertension, and stage 2 hypertension were 1.39 (0.93–2.07)(P = 0.107), 1.59 (1.17–2.17)(P = 0.003), and 2.38 (1.82–3.12)(P <0.001) in the ≤45 years group and 1.13 (0.97–1.32)(P = 0.111), 1.20 (1.06–1.34)(P = 0.003), and 1.72 (1.57–1.87)(P <0.001) in the >45 years group. Conclusion: Newly defined stage 1 hypertension is independently associated with CAC progression in asymptomatic Korean adults irrespective of different age groups.